A Traditional Chinese Medicine Formula Danshen Baibixiao Ameliorates Imiquimod-Induced Psoriasis-Like Inflammation in Mice - Jin, Xiaoqi; Xu, Hongfeng; Huang, Chuanqi; Ma, Haoran; Xiong, Xin; Cheng, Lu; Wang, Fuqian; Feng, Yan; Zhang, Geng (Frontiers in Pharmacology, 2021)
Abstract Background: Danshen Baibixiao (DB) is a traditional Chinese medicine formula, which has been used to treat psoriasis for decades. Although DB shows good efficacy in clinical practice, the pharmacological effects and underlying mechanisms of DB remain elusive. This study aimed to evaluate the anti-psoriatic effects of DB and explore its underlying mechanisms in an imiquimod (IMQ)-induced psoriasis-like mouse model. Materials and methods: DB was orally administered on IMQ-induced psoriatic mice. Psoriasis area severity index (PASI) was used to evaluate the severity of the inflammation in skin, and histological changes were evaluated by hematoxylin and eosin (H&E) staining. Levels of inflammatory cytokines, such as tumor necrosis factor α (TNF-α), interleukin (IL)-17A, IL-23, IL-6, IL-1β and IL-22 in serum were assessed by enzyme-linked immunosorbent assay (ELISA). mRNA expressions of IL-17A, IL-23, IL-6 and IL-22 were determined by real-time polymerase chain reaction (PCR). Expression levels of proteins related to NF-κB, STAT3 and MAPKs signaling pathways were measured by western blotting (WB). Results: DB significantly ameliorated the psoriatic symptoms in IMQ-induced mice. The serum levels of inflammatory cytokines (TNF-α, IL-17A, IL-23, IL-6, IL-1β and IL-22) were decreased, and mRNA expressions of IL-17A, IL-23, IL-6 and IL-22 in skin tissues were down-regulated. Moreover, WB analysis indicated that DB inhibited the activation of NF-κB, STAT3 and MAPKs signaling pathways. Conclusions: This study confirms the anti-psoriatic activity of DB in IMQ-induced psoriasis-like mice. The possible mechanism may relate to the activities of regulating the IL-23/TH-17 axis and suppressing the activation of NF-κB, STAT3 and MAPKs signaling pathways.